Evaluation of Diplopia Complicated by Advanced Visual Field Loss: A Clinical Application of Luster Testing. - Gobeille, Micaela; Patel, Shephali; Meltzer, Bradley; Fischer, Michael (Optometry & Visual Performance, 2020)
Background: Visual field constriction and binocularity may interact in such a way that slight ocular misalignments produce diplopia due to a loss of peripheral fusional lock. Limited research has characterized diplopia in visual field constriction, and existing case reports do not evaluate patients' fusion. In this paper, we discuss the prismatic management of a patient with significant visual field loss secondary to retinitis pigmentosa. We present a framework to allow simple and efficient clinical evaluation of fusion in this population. Case Report: A 74-year-old male presented with an ocular history of advanced retinitis pigmentosa and a visual complaint of diplopia that manifested as difficulty focusing with changes in gaze. His habitual bifocals contained a total of 4Δ base in. A red acetate lens over the right eye and a penlight were used to evaluate binocularity on four separate office visits. Luster was used to assess fusion and enabled a continuous suppression check throughout testing. Multiple evaluations were conducted during each office visit, as the patient's responses were variable. Fresnel prisms were trialed between office visits to ensure that prismatic correction was adequate. Ultimately, a total of 1.5Δ base in, split between the two eyes, was needed to achieve luster. The patient noted significant improvement in symptoms with the updated prismatic correction and achieved luster with his new bifocals. Conclusions: Luster testing can be an effective way to assess binocularity in patients with significant visual field constriction and is an easily accessible evaluation technique for most clinicians. Some patients with visual field constriction can be adequately corrected with prism, although due to the progressive nature of ocular disease, the amount of prism needed is expected to change over time. Further research on the prevalence and underlying mechanism of diplopia in patients with visual field constriction is needed.